Keeping Talent Close: A Deep Dive into Employee Retention in the Malaysian Financial Industry - Chinn, Michele Chong Sheau; Bhardwaj, Rajeev; Lary, Alaa; Senathirajah, Abdul Rahman bin S; Haque, Rasheedul; Nazneen, Afroze (Journal of Ecohumanism, 2025)
The aim of this manuscript is to examine the key factors influencing employee retention in the Malaysian financial industry. The conceptual model for this study was developed based on previous research in the field of financial industry in Malaysia and globally. The conceptual model has four variables that affect employee retention which are salary, supervision, responsibility and career advancement. The underpinning theory used in this study is the Two Factor Theory of Motivation. A survey instrument in the form of a structured questionnaire was designed based on a careful review of pertinent literature. This study collected empirical data from 78 respondents based on purposive sampling. Multiple regression analysis is used to test the significance of the research model. The findings reveal that all the four variables of which the two motivators and two hygiene factors have an influence on the employee retention of Malaysian financial institutions (FIs). The implication drawn from this study aids human resource managers in the financial industry to focus their resources and design appropriate strategies on the key variables uncovered in this study to improve employee retention i.e. reduce the employee turnover. The key value of this research lies in its findings of the influence of employee retention in Malaysia which is currently under researched.